MODERNISASI PENDIDIKAN ISLAM INDONESIA PENGALAMAN NAHDLATUL ULAMA - Muhammedi Muhammedi (JURNAL TARBIYAH, 2016)
This paper aims to present and describe the modernization of Islamic education: the experience of Indonesia Nahdlatul Ulama from the philosophical aspect, objectives, curriculum, methods, human resources, institutional, and influence and contributions. The modernization of education NU can not be released from the LP. NU Ma'arif which serve as executors of policies in the field of education and teaching of NU, both formal and non formal. Meanwhile the RMI (Rabitha Ma'ahid Al-Islamiyah) who is in charge of implementing the policy in the field of educational system development of NU and boarding schools. So the implementation of education among NU terkoordinir really well.Keywords: Modernization, Education, Nahdlatul Ulama